2018
DOI: 10.1557/jmr.2018.6
|View full text |Cite|
|
Sign up to set email alerts
|

Piezoelectric polymer thin films with architected cuts

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
17
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 40 publications
0
17
2
Order By: Relevance
“…[20][21][22][23][24][25] The out-of-plane buckling behavior of thin hierarchical kirigami sheets remains largely unexplored, and the only closely related study focuses on a system in which patterned notches are introduced in addition to cuts to guide the pop-up in a preferred direction. We find that for sufficiently small thicknesses, the behavior is completely different from that previously reported for thick sheets, [20][21][22][23][24][25][26][27][28][29][30] as mechanical instabilities triggered by the applied deformation result in the formation of complex 3D patterns and sequential pop-up processes. We first use a combination of experiments and numerical simulations to study the response under uniaxial tension of kirigami sheets with hierarchical cuts arranged to form an array of squares connected at their vertices via thin ligaments and investigate in detail both the effect of geometry as well as plasticity of the sheets.…”
contrasting
confidence: 88%
See 1 more Smart Citation
“…[20][21][22][23][24][25] The out-of-plane buckling behavior of thin hierarchical kirigami sheets remains largely unexplored, and the only closely related study focuses on a system in which patterned notches are introduced in addition to cuts to guide the pop-up in a preferred direction. We find that for sufficiently small thicknesses, the behavior is completely different from that previously reported for thick sheets, [20][21][22][23][24][25][26][27][28][29][30] as mechanical instabilities triggered by the applied deformation result in the formation of complex 3D patterns and sequential pop-up processes. We first use a combination of experiments and numerical simulations to study the response under uniaxial tension of kirigami sheets with hierarchical cuts arranged to form an array of squares connected at their vertices via thin ligaments and investigate in detail both the effect of geometry as well as plasticity of the sheets.…”
contrasting
confidence: 88%
“…We first use a combination of experiments and numerical simulations to study the response under uniaxial tension of kirigami sheets with hierarchical cuts arranged to form an array of squares connected at their vertices via thin ligaments and investigate in detail both the effect of geometry as well as plasticity of the sheets. We find that for sufficiently small thicknesses, the behavior is completely different from that previously reported for thick sheets, [20][21][22][23][24][25][26][27][28][29][30] as mechanical instabilities triggered by the applied deformation result in the formation of complex 3D patterns and sequential pop-up processes. We then show that the geometric parameters of the embedded hierarchy enable us to tune both the morphology of the buckling-induced 3D patterns as well as the stress-strain response of the surfaces.…”
contrasting
confidence: 66%
“…Using architected cuts doesn't require changing the material or overall dimensions, making it attractive for applications in self-powered devices with design constraints. [1]…”
mentioning
confidence: 99%
“…[7][8][9] Therefore, the Kirigami structures have been adopted to many applications, especially sensors, [10,11] energy storage, [12] actuator, and robotics. [13] To the best of our knowledge, although there are few works aiming to harvest ambient energy using Kirigami structure, [14,15] no study has yet reported an implantable energy harvester built based on this concept. [16] In our work, combining the advantage of the PVDF-TrFE composite material with remarkable energy conversion efficiency, we developed a Kirigami-inspired piezoelectric composite patch.…”
Section: Introductionmentioning
confidence: 99%
“…[ 7–9 ] Therefore, the Kirigami structures have been adopted to many applications, especially sensors, [ 10,11 ] energy storage, [ 12 ] actuator, and robotics. [ 13 ] To the best of our knowledge, although there are few works aiming to harvest ambient energy using Kirigami structure, [ 14,15 ] no study has yet reported an implantable energy harvester built based on this concept. [ 16 ]…”
Section: Introductionmentioning
confidence: 99%